Semiotic Misinterpretation of Tai Chi Symbols in Tea Packaging: Cultural Impact and Design Strategies (Architecture Image Studies, 2025)
Tai Chi symbols are widely used in tea packaging; however, their cultural significance is often disconnected from the products they represent. While these symbols hold profound philosophical and historical meanings in Chi-nese culture, their commercialization in packaging design frequently results in misinterpretations that diminish their authenticity. This research looked at the mistaken interpretations of Tai Chi symbols in semiotics while it stud-ied their improper use against cultural identity, brand evaluation, and con-sumer connection. The research conducted an exploratory qualitative case study analysis on 46 tea packaging designs from the Chinese mainstream online markets. This research design chose cases according to market reach, branding, and symbolic complexity. Saussure’s Signifier-signified relation-ships provided the theoretical basis for conducting a descriptive analysis in two phases, including categorizing the visual elements of Tai Chi symbols and the semantic analysis through design element frequency data analysis. The findings indicated four critical issues in applying Tai Chi symbols in tea packaging design: poor strategic placement and inappropriate sizing reduced their recognizability; excessive visual standardization diminished their cul-tural depth; overused commercialization trivialized their philosophical and aesthetic value, destroying cultural authenticity; and the widespread aesthet-ic fatigue reducing engagement and diminishing brand perceived unique-ness.This study emphasized that respecting cultural symbols' historical and philo-sophical connotations demands that products match the intrinsic values em-bedded in cultural symbols. The main contribution of this study was to de-velop a semiotic framework that allowed designers to manage the commer-cial-authenticity conflict by letting them reinterpret Tai Chi symbols in planned ways that combined cultural accuracy with heritage protection. Therefore, this culturally sensitive design method can strengthen brand nar-rative and cultural communication effectiveness, attract consumers, and cre-ate significant market value.